Electromagnetic field excitation by an electron bunches in a partially filled cylindrical dielectric resonator - Galaydych, K.V.; Sotnikov, G.V.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2015)
A nonlinear self-consistent theory of wakefield excitation by an electron bunches in cylindrical resonator with longitudinally nonuniform filling by dielectric is constructed. A bunch-excited field are presented in the form of superposition solenoidal and potential fields. The formulated nonlinear theory allows carrying out numerical analysis of resonator excitation by electron bunches for the best interpretation of the results received in experiment.